2016
DOI: 10.1099/mic.0.000180
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of oligomeric assembly of colonization factor CS6 from enterotoxigenic Escherichia coli

Abstract: The widely distributed colonization factor (CF) CS6 of enterotoxigenic Escherichia coli (ETEC) has gained importance over the years in terms of its structure and function. CS6 is an afimbrial assembly in contrast to the other ETEC CFs, which are mostly fimbrial. A recent study predicted a linear fibre model for recombinant chimeric CS6 and formation of oligomers in solution. In this study, we characterized the oligomeric assembly of CS6, purified from a clinical ETEC isolate and identified its existence in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Expression, purification, and characterization of "homologous donor strandcomplemented" CS6-derived recombinant proteins. It has been observed that purified CS6 (21) as well as its CssA and CssB subunits (S. J. Savarino, unpublished data) form oligomeric complexes in solution. This has also been described for the class 5 major fimbrial subunit CfaB, which multimerizes via donor strand interactions between two subunits (27).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Expression, purification, and characterization of "homologous donor strandcomplemented" CS6-derived recombinant proteins. It has been observed that purified CS6 (21) as well as its CssA and CssB subunits (S. J. Savarino, unpublished data) form oligomeric complexes in solution. This has also been described for the class 5 major fimbrial subunit CfaB, which multimerizes via donor strand interactions between two subunits (27).…”
Section: Resultsmentioning
confidence: 98%
“…Instead, CS6 is afimbrial in structure, associating closely with the bacterial cell surface instead of extending from the surface as is typical of the fimbrial CFs (11). Furthermore, it is made up of two structural subunits, CssA and CssB, in a 1:1 ratio (21). The bioassembly of CS6 is encoded by a plasmid-associated operon consisting of four genes (cssABCD) that is transcribed as a single transcript.…”
mentioning
confidence: 99%
“…Thereafter, the CssA C -CssB N interaction is then driven in the presence of CssD through DSE. The final outcome is a spherical, hetero-oligomeric complex of (CssA-CssB) n on the bacterial outer surface (19).…”
Section: Discussionmentioning
confidence: 99%
“…Since CS6 forms concentration-dependent oligomers in solution (10,19), we analyzed the oligomer formation of those mutant CS6 proteins that were expressed on the bacterial cell surface at reduced levels. Three CssA mutC proteins, i.e., the G141A, V149A, and Y151A mutants, showed disruption in the oligomeric pattern, whereas the other two mutant proteins, i.e., the I142A and Y152A mutants, did not show any oligomeric pattern.…”
Section: Effects Of Alanine Substitutions On Cs6 Oligomerizationmentioning
confidence: 99%
“…In contrast to the other ETEC CFs that are fimbrial, CS6 is afimbrial. CS6 consists of two tightly-associated subunits CssA and CssB, organised in an equal (1:1) ratio, to form an external array of higher-order oligomers [9].…”
Section: Introductionmentioning
confidence: 99%